Elementary School Students' Mental Health during the Corona Virus Pandemic (COVID-19) - Elisabeth Desiana Mayasari; Laurensia Aptik Evanjeli; Brigitta Erlita Tri Anggadewi; Puji Purnomo (Universitas Pendidikan Ganesha, 2021)
During the Coronavirus (COVID-19) pandemic, changes in routine have affected students’ psychological development. This study aims to determine elementary school students’ mental health during the Corona Pandemic. The benefit of this research is as a basis for efforts to prevent and overcome unexpected psychological conditions in students. This research is a descriptive quantitative study using a survey method. The population in this study were 148 students aged 9-14 years. The data collection technique used was a questionnaire. This study used the Indonesian version of Strength and Difficulty Questionnaire for Children (SDQC) arranged by Robert Goodman. The result showed that the condition of the students was in the